THEME PATTERNS IN INTRODUCTION SECTIONS OF RESEARCH ARTICLES WRITTEN BY UNDERGRADUATE STUDENTS - Afriani Afriani; Refnaldi Refnaldi (Universitas Negeri Padang, 2019)
This study analyzed theme patterns of 41 introduction sections of research articles written by undergraduate students of Indonesia, especially students of the English department in Universitas Negeri Padang. The sources of data are from e-journal archives of E-journal English Language and Literature (JELL) and Journal of English Language Teaching (JELT) of Universitas Negeri Padang. The data were analyzed by classifying the theme and rheme structure of clause sequences and then determining the patterns. This research is a descriptive study with a qualitative approach. The result of the findings shows that a simple linear pattern (42,70%) found to be the most dominant pattern of the theme found in the data. In addition, new patterns (27,35%) are also frequently used in the data. These findings indicate that most students tend to write their ideas more cohesive than coherent as the lack of using an interpersonal theme and derived hyper-theme pattern found in the data.